Estimation of minimum working capital for construction projects in Malaysia - Hassim, S.; Kadir, M.R.A.; Lew, Yoke-Lian; Sim, Yin-Chew (American Society of Civil Engineers (ASCE), 2003)
Forecasting cash requirements is essential for all contractors during the tendering stage since cash flow at the beginning of the project is a major cause of construction companies' failure. Unfortunately, estimating minimum working capital (MWC) is not the mainstream practice of the majority of contractors in Malaysia, who find that the present models for estimating MWC are cumbersome and seldom give an accurate estimate. Therefore estimates of MWC made during the tendering stage need to be simplified so they can be prepared quickly with minimum input. It is important for the developer or owner to select a qualified contractor with competent financial backing. This paper establishes the relationship among the factors that contribute to MWC requirements and presents a simple model that could be used as a guide to estimate MWC for housing construction projects in Malaysia. The estimation is based on percentages of variables of contract value based on the historical data that influence MWC; the MWC obtained is then expressed in terms of percentage of contract value.